915 Post-Nephrectomy Recurrence Rates in T3 Renal Cell Carcinoma Over A 10-Year Period. (4th May 2021) - Okwu, N; Gooneratne, S; Piedad, J; Akhtar, M
Abstract: Introduction: The objective of the study was to estimate the post-nephrectomy recurrence rate and assess practice around peri-op investigation and treatment. Method: Imaging, histopathology, and clinical data were gathered using electronic and paper medical records of patients who underwent nephrectomy for T3 RCC. Recurrence defined as local recurrence. Results: Fifty-one patients with T3 RCC were identified, 74.5% of whom were male with a median age 71 (range 45-91). One-third had metastatic disease. The majority (96.0%) underwent radical nephrectomy with adrenalectomy (49.0%) and lymph node dissection (19.6%). Clear cell RCC was the main histopathological type (92.2%) with chromophobe making up 3.9%. At year one there was recurrence in 20.0% of patients at a median time of 5months (range 1-10, 90.0% grade 3, 10% grade 4). At year five recurrence was identified in 16.7% in a median time 50months (range 41-56; 50% grade 2 and 3 each). Ten-year follow-up identified recurrence in 85.7% at a median time 64.5 months (range 62-91; 50% grade 2 and 3 each) with the remaining patient developing jejunal metastatic recurrence in 168 months. Adjuvant treatment was administered in 57.1%. Conclusions: Establishing the right time to follow-up patients especially males, 17 months median recurrence time with the most frequently occurring was clear cell RCC.